Admission triglyceride-glucose index predicts long-term mortality patients with subarachnoid hemorrhage a retrospective analysis of the MIMIC-IV database - Zhuangbin Liao; Heng Lin; Siwei Liu; Paul R. Krafft (Brain Hemorrhages, 2024)
Objective：The triglyceride-glucose (TyG) index is an indicator for insulin resistance (IR). Several studies have validated the impact of the TyG index on cerebrovascular disease. However, the value of the TyG index in patients with subarachnoid hemorrhage (SAH), requiring admission to the intensive care unit (ICU), remains unclear. In this study, we aimed to investigate the relationship between the TyG index and clinical outcomes in SAH patients. Methods：: In this study, we identified patients with severe SAH requiring ICU admission from the Medical Information Marketplace for Intensive Care (MIMIC-IV) database. These patients were then categorized into tertiles based on their TyG index levels. After adjusting for confounders, multivariate Cox proportional hazards analysis and restricted cubic spline analysis were performed to assess the relationship between the TyG index and clinical outcomes in critically ill SAH patients. Results：: The study outcomes included in-hospital mortality and ICU mortality. The rate of in-hospital mortality and ICU mortality were 16.8 % and 13.1 %, respectively. After adjusting for confounders, multivariate Cox proportional hazards analysis showed that an elevated TyG index was significantly associated with all-cause mortality. Specifically, patients with a high TyG index had a significantly higher risk of in-hospital mortality (adjusted hazard ratio: 1.72; 95 % confidence interval: 0.81–3.66; P = 0.16) and ICU mortality (adjusted hazard ratio: 2.60; 95 % confidence interval: 1.04–6.43; P = 0.039). The TyG index was most strongly associated with ICU mortality. Moreover, restricted cubic spline curves demonstrated a progressive increase in the risk of all-cause mortality with an increase in the TyG index. Conclusion：: Overall, our findings suggest that the TyG index may be a useful tool in identifying SAH patients at a higher risk of all-cause mortality in both, the hospital and the ICU setting.